2017
DOI: 10.1093/ofid/ofx202
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Ruxolitinib in STAT1 Gain-of-Function-Associated Severe Fungal Disease

Abstract: Heterozygous STAT1 gain-of-function (GOF) mutations are associated with chronic mucocutaneous candidiasis and a broad spectrum of infectious, inflammatory, and vascular manifestations. We describe therapeutic failures with the Janus Kinase (JAK) inhibitor ruxolitinib in 2 STAT1 GOF patients with severe invasive or cutaneous fungal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 18 publications
2
49
0
Order By: Relevance
“…Interestingly, other STAT1 GOF related disorders, such as alopecia and enteropathy have also shown considerable improvement with JAK1/2 inhibitors . In contrast to these reports, two adult patients with severe dermatophytosis and disseminated coccidioidomycosis due to STAT1 GOF mutation were recently reported to fail to respond to ruxolitinib . In our study, one of the patients was treated with ruxolitinib, 10 mg twice daily, due to aortic calcification which is believed to be driven by IFN .…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, other STAT1 GOF related disorders, such as alopecia and enteropathy have also shown considerable improvement with JAK1/2 inhibitors . In contrast to these reports, two adult patients with severe dermatophytosis and disseminated coccidioidomycosis due to STAT1 GOF mutation were recently reported to fail to respond to ruxolitinib . In our study, one of the patients was treated with ruxolitinib, 10 mg twice daily, due to aortic calcification which is believed to be driven by IFN .…”
Section: Discussionmentioning
confidence: 58%
“…However, major adverse effects, such as infection and a cytokine rebound effect, have been reported in patients treated with ruxolitinib for STAT1 GOF mutations and other conditions (126)(127)(128). Recently, an international retrospective study on a cohort of 15 patients with STAT1 GOF mutations who received HSCT showed poor overall survival (40%) and poor event-free survival (10%) (129).…”
Section: Stat1mentioning
confidence: 99%
“…In STAT1 and STAT3 ‐GOF, treatment with JAK inhibitors (i.e., ruxolitinib, tofacitinib, and baricitinib) may reduce the burden of autoimmune disease (e.g., immune cytopenias) and IL‐6 R antagonists (i.e., tocilizumab) used alone or in combination with JAK inhibitors in STAT3 ‐GOF reduces the burden of autoimmune disease, lymphoproliferation, and hyperinflammation . Increased risk of invasive fungal infections needs to be considered when considering addition of JAK inhibitors for the management of immune dysregulation …”
Section: Primary Immune Regulatory Disorders Spectrum: Alps‐like/ipexmentioning
confidence: 99%